Paesaggi urbano-portuali del grano. Magazzini e silos nel golfo di Napoli (1779-1967) - Parisi, Roberto (OS. Opificio della Storia, 2023)
The essay deals with the theme of urban-port landscapes of wheat in Italy through the case study of Naples and its gulf. Starting from the scientific debate that develops in Italy around the early thirties of the twentieth century, the author traces in a long-term perspective the main architectural typologies of the port silos built in the Gulf of Naples, by the Bourbon Warehouses designed by Ferdinando Fuga in the late eighteenth century to the ‘modern’ cylindrical reinforced concrete silos which were built during the twentieth century in the seaports of Naples, Castellammare di Stabia and Torre Annunziata.